The Influence of Kaizen Culture, Work Discipline on Productivity with Implementation of Employee Performance at PT. Mandom Indonesia - Camelia Aisyah Amini; Rahmat Hidayat (Kontigensi : Jurnal Ilmiah Manajemen, 2023)
The aim of this research is to find out whether the performance of PT Mandom Indonesia and its kaizen culture influence productivity or not. The total population in this study was 128 people with the determination of the number of samples using the Slovin formula which produced 114 respondents. This study uses the Structural Equation Modeling (SEM) analysis model to determine how much independent influence the dependent variable has through the intervening variables, carried out using the Lisrel 8.8 program. The results of this study prove that the kaizen culture has a significant and positive effect on productivity. Productivity is significantly and positively influenced by work discipline. Performance is not significantly affected by the kaizen culture. Performance is significantly affected by work discipline. Efficiency has a significant effect on execution. Productivity is significantly and positively influenced by the kaizen culture and work discipline. Kaizen culture, work discipline, and efficiency have a significant effect on execution.